Debating education : is there a role for markets? - Brighouse, Harry; Harry,Brighouse (UK: Oxford University Press, 2020)
"Science is both a creative endeavor and a highly regimented one. It involves surprising, sometimes unthinkably novel ideas, along with meticulous exploration and the careful exclusion of alternatives. At the heart of this productive tension stands a human capacity typically called "the imagination": our ability, indeed our inclination, to think up new ideas, situations, and scenarios and to explore their contents and consequences in the mind's eye. This volume explores our capacity to imagine and its implications for the philosophy and practice of science. One central aim is to integrate philosophical and psychological philosophical viewpoints and to assess central questions both empirically and theoretically. Such questions include the roles of models, metaphors, and thought experiments; the correct way to understand scientific fictions; the development of imaginative capacities; and the connection between the imagination and scientific practices such as abstraction, idealization, and counterfactual reasoning"--
Keywords: Education -- Philosophy